2007
DOI: 10.1124/jpet.106.117622
|View full text |Cite
|
Sign up to set email alerts
|

Epothilone B Inhibits Neointimal Formation after Rat Carotid Injury through the Regulation of Cell Cycle-Related Proteins

Abstract: The abnormal proliferation of vascular smooth muscle cells (VSMCs) in arterial walls is an important pathogenetic factor of vascular disorders such as atherosclerosis and restenosis after angioplasty. Epothilone B, a novel potential antitumor compound, has a potent effect on preventing postangioplasty restenosis. Therefore, we established an in vivo rat carotid injury model and examined the potential effects of epothilone B on cardiovascular disease. We found that epothilone B potently prevented neointimal for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
3
10
0
Order By: Relevance
“…PDGF-BB initiates a multitude of biological effects through the activation of intracellular signal transduction pathways that contribute to VSMC proliferation, migration, and collagen synthesis [17,18]. Animal experiments demonstrated that increasing levels of PDGF after arterial injury correlated with neointimal cellular proliferation [19,20,21]. Targeting PDGF with an anti-PDGF antibody [22], targeting the expression of the receptor with antisense oligonucleotides [23], or using inhibitors of PDGF signal transduction [24] have all been shown to attenuate neointima development.…”
Section: Discussionmentioning
confidence: 99%
“…PDGF-BB initiates a multitude of biological effects through the activation of intracellular signal transduction pathways that contribute to VSMC proliferation, migration, and collagen synthesis [17,18]. Animal experiments demonstrated that increasing levels of PDGF after arterial injury correlated with neointimal cellular proliferation [19,20,21]. Targeting PDGF with an anti-PDGF antibody [22], targeting the expression of the receptor with antisense oligonucleotides [23], or using inhibitors of PDGF signal transduction [24] have all been shown to attenuate neointima development.…”
Section: Discussionmentioning
confidence: 99%
“…RASMCs were isolated by enzymatic dispersion according to a previously reported method (Lim et al, 2007), with some modifications. Cells were cultured in Dulbecco's modified Eagle medium (DMEM) supplemented with 10% FBS, 100 IU/mL penicillin, 100 µg/ mL streptomycin, 8 mM HEPES and 2 mM L-glutamine at 37 o C in a humidified atmosphere of 95% air and 5% CO 2 .…”
Section: Cell Culturementioning
confidence: 99%
“…DNA synthesis was determined by a [ 3 H]-thymidine incorporation assay as previously described (Lim et al, 2007). In brief, RASMCs were seeded in 24-well plates.…”
Section: Dna Synthesis Assaymentioning
confidence: 99%
See 2 more Smart Citations